First pass isolation predicts clinical success after contact force guided paroxysmal atrial fibrillation ablation. (25th November 2020) - Osorio, J; Hunter, T.D; Rajendra, A; Zei, P; Morales, G
Abstract: Background: Contact force (CF) ablation of AF with a focus on catheter-tissue contact stability optimizes clinical success and may help the operator to achieve pulmonary vein (PV) isolation in a single encirclement. While it seems evident that first pass isolation reduces procedure time, the effect on long term clinical success has not been reported. Purpose: To evaluate the relationship between first pass isolation and freedom from atrial tachyarrhythmia recurrence at 1 year after PAF ablation. Methods: Consecutive de novo PAF ablations were performed with a porous tip contact force catheter in 2017. All ablations used wide-area circumferential ablation and first pass isolation was captured separately for the left and right PVs. CF was held between 10–20 g and the catheter was moved every 10–20 s. RF energy was set at 40W throughout the atrium. Clinical success was defined as freedom from recurrent atrial tachyarrhythmia through 1 year following a 90-day blanking period and freedom from reablation at any time through 1 year. Results: The population included 157 patients, age 62.7±11.5, 54.8% male, with mean CHA2DS2-VASc score of 2.3±1.5. Mean procedure times were 76.2±29.8 minutes and 89.2% of the ablations were performed with no fluoroscopy. The overall clinical success rate at 1 year was 86.1%. The number of ipsilateral PV pairs that could be isolated in a single pass was significantly associated with 1-year success (p=0.0043). Achieving first pass isolation on even one ipsilateral PV pair vs. neither pair was significantly associated with clinical success (Table). Conclusion: In a real-world setting, first pass isolation on at least one PV side was predictive of 1 year clinical success in a PAF population ablated with CF. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Biosense Webster, Inc.